Development of Measurement Tool for Understanding, Application, and Reasoning Mathematics of Madrasah Ibtidaiyah Students - Ismail, Ilyas; Nursalam, Nursalam; Angriani, Andi Dian; Kusumayanti, Andi (Jurusan Matematika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Sema, 2021)
This study aims to develop a measurement tool for students' understanding, application and mathematical reasoning ability at Madrasah Ibtidaiyah in South Sulawesi. This research is a formative research type of Research and Development (R&D) research through 4 (four) stages, namely: the preliminary stage; the stage of self evaluation (curriculum analysis, material, students) and design; prototyping stage (validation, evaluation and revision) which includes expert reviews, one-to-one and small groups; and the feld test stage. The product of this research was an assessment instrument in the form of questions that measured the ability of understanding, application, and mathematical reasoning of Madrasah Ibtidaiyah students. The test subjects in this study were fourth grade MI students in Makassar City, Gowa regency, and Sinjai regency. The results of the content validity based on the rater indicated that the test items needed were declared valid after being assessed by the rater and analyzed using the CVR (Content Validity Ratio) and CVI (Content Validity Index). In the reliability test, the results of the analysis conducted for multiple choice questions and the contents were in the category of